2016
DOI: 10.5267/j.ijiec.2015.8.001
|View full text |Cite
|
Sign up to set email alerts
|

Flow shop scheduling algorithm to optimize warehouse activities

Abstract: Successful flow-shop scheduling outlines a more rapid and efficient process of order fulfilment in warehouse activities. Indeed the way and the speed of order processing and, in particular, the operations concerning materials handling between the upper stocking area and a lower forward picking one must be optimized. The two activities, drops and pickings, have considerable impact on important performance parameters for Supply Chain wholesaler companies. In this paper, a new flow shop scheduling algorithm is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Naturally, the time required by these operations will depend on the type of product being processed (quantity, weight, volume, and shape of parts, components and final products). Centobelli et al (2016) provide further insight on the subject material handling in warehouses.…”
Section: Problem Presentationmentioning
confidence: 96%
“…Naturally, the time required by these operations will depend on the type of product being processed (quantity, weight, volume, and shape of parts, components and final products). Centobelli et al (2016) provide further insight on the subject material handling in warehouses.…”
Section: Problem Presentationmentioning
confidence: 96%
“…Cross-docking facilities play an important role in JIT/JIS trans-shipment processes, where inventory backups and delays must be avoided. Lot sizing is an important research field related to the topic of our research work; the most relevant publications are focusing on a flow shop scheduling algorithm for warehouse activities [52], inventory control optimization in the case of flexible demand [53] and optimization of just-in-time logistics network problems under uncertainties [54]. Researchers showed that trans-shipment with supplier and customer time windows where flow is constrained by transportation schedules and warehouse capacities can be optimized with the objective to minimize costs, including inventory costs [55].…”
Section: Content Analysismentioning
confidence: 99%
“…The probability of state transfer is obtained by formula (1). In the calculation process, ij η represents the visibility of two pick-up locations.…”
Section: Operation Design Of Dynamic Ant Colony Genetic Algorithmmentioning
confidence: 99%
“…The manufacturers strictly control the production of related aspects, trying to reduce production costs. However, warehousing management is an important task of enterprises [1]. The problem of stock efficiency has gradually become the focus of attention of the enterprises, and the stocking work has become the hot spot of the research of the scholars at present [2].…”
Section: Introductionmentioning
confidence: 99%